EFEKTIVITAS PENGELOLAAN LIMBAH CAIR MEDIS DI PUSKESMAS SAKRA BARAT KABUPATEN LOMBOK TIMUR BERDASARKAN PERMEN LH NO. 68 TAHUN 2016: EFEKTIVITAS PENGELOLAAN LIMBAH CAIR MEDIS DI PUSKESMAS SAKRA BARAT KABUPATEN LOMBOK TIMUR BERDASARKAN PERMEN LH NO. 68 TAHUN 2016 - Hariady, M. Rifky Hariady; muhammad iman, darmawan (Fakultas Teknik Universitas Hamzanwadi, 2025)
The management of medical liquid waste is an important aspect in efforts to maintain environmental quality and public health. This study aims to analyze the effectiveness of medical liquid waste management at the Sakra Barat Health Center, East Lombok Regency, based on quality standards set forth in the Ministry of Environment Regulation No. 68 of 2016. The research method used is a quantitative approach with testing of waste samples before and after treatment in the Wastewater Treatment Installation (IPAL). The results show that before treatment, several waste parameters such as BOD (139 mg/l), COD (825 mg/l), and TSS (282 mg/l) exceeded the established quality standards. However, after treatment, these values significantly decreased and met the quality standards, with TSS values of 2.50 mg/l at an effectiveness percentage of 99.11%, BOD of 1.53 mg/l at an effectiveness percentage of 98.90%, COD of 38.0 mg/l at an effectiveness percentage of 95.39%, and a pH value of 7.26. This indicates that the IPAL at the Sakra Barat Health Center is effective in processing medical liquid waste, ensuring that the discharged waste is safe and does not pollute the environment.